2012
DOI: 10.1590/s1806-37132012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Responsividade do teste do degrau de seis minutos a um programa de treinamento físico em pacientes com DPOC

Abstract: Objective: To evaluate the responsiveness of the six-minute step test (6MST) to an aerobic physical training program (PTP) and to determine the efficacy of the PTP regarding spirometric variables during the 6MST, as well as physical performance, sensation of dyspnea, and SpO 2 during the 6MST and the six-minute walk test (6MWT), in patients with COPD. Methods: This was a controlled, prospective randomized study involving patients clinically diagnosed with COPD, with an FEV 1 /FVC ratio < 70%, and having been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…Several studies reported that the degree of desaturation was less on the 6minStepper than on 6MWT (SpO 2 2.3 to 3% more desaturation on 6MWT, 4 studies). 64 , 71 , 76 , 81 Desaturation on the 6MST with free cadence was not different to 6MWT 52 or CPET. 62 A 15-step oximetry test resulted in similar desaturation to a 6MWT in patients with idiopathic pulmonary fibrosis (mean nadir SpO 2 86(SD 8)% vs 86 (7)%).…”
Section: Step Testsmentioning
confidence: 71%
See 1 more Smart Citation
“…Several studies reported that the degree of desaturation was less on the 6minStepper than on 6MWT (SpO 2 2.3 to 3% more desaturation on 6MWT, 4 studies). 64 , 71 , 76 , 81 Desaturation on the 6MST with free cadence was not different to 6MWT 52 or CPET. 62 A 15-step oximetry test resulted in similar desaturation to a 6MWT in patients with idiopathic pulmonary fibrosis (mean nadir SpO 2 86(SD 8)% vs 86 (7)%).…”
Section: Step Testsmentioning
confidence: 71%
“…Of the 128 full text papers screened, 84 were included (85 reports). This included five studies examining the 6MWT, 7 11 39 studies examining STS tests, 12 50 35 studies examining step tests 19 , 24 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…The 6MST has shown to be clinically useful in estimating exercise tolerance in COPD 34 , and requires minimal physical space and only two evaluators to perform the test 8 , 16 . It is noteworthy that the 6MST, compared to 6MWT, uses specific muscle groups (quadriceps).…”
Section: Discussionmentioning
confidence: 99%
“…Outra hipótese plausível para esse resultado é a de que, no teste do degrau, há uma maior participação da musculatura das articulações dos membros inferiores, percebendo-se o envolvimento de diferentes ângulos capazes de provocar alterações na resposta pressórica. Além disso, vale ressaltar que diferentemente do TC6m, em que há apenas um componente horizontal no trabalho executado, no teste do degrau há o acréscimo do componente de deslocamento vertical, o que tende a aumentar o nível de exigência do mesmo 19 .…”
Section: Resultsunclassified